2018
DOI: 10.1016/j.jjcc.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic wall strain is associated with incident heart failure in African Americans: Insights from the atherosclerosis risk in communities study

Abstract: DWS was independently associated with an increased risk of incident HF in a community-based cohort of African Americans. DWS could be used as a qualitative estimator of LV myocardial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that pulse wave velocity was increased in patients with PAD [21]. Notably, increased arterial stiffness has also been reported to be associated with LV myocardial stiffness and LV diastolic dysfunction [22][23][24]. Arterial stiffening increases LV [ ( F i g .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that pulse wave velocity was increased in patients with PAD [21]. Notably, increased arterial stiffness has also been reported to be associated with LV myocardial stiffness and LV diastolic dysfunction [22][23][24]. Arterial stiffening increases LV [ ( F i g .…”
Section: Discussionmentioning
confidence: 99%
“… [42] also suggested that antagonistic interaction is expected to occure if two risk factors share some common pathways in the pathogenesis of the disease outcome, and some of the specific pathways are saturated by either risk factor. It has previously been noted that elevated hs-TnT and low ABI share some common pathways, such as left ventricular dysfunction and hypertrophy [ 43 , 44 ], that were shown to subsequently lead to the development of cardiovascular events [ 45 , 46 ]. Additive interaction is relevant in translating findings to disease prevention [ 24 , 37 , 47 ]; however, it was found to be absent in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between DWS and LV myocardial stiffness constant which is the gold standard to evaluate LV myocardial stiffness, was proved only in a basic experimental study and a correlation of only 0.4 does not "prove" that the LV myocardial stiffness could be accurately reflected by DWS. In addition, despite the animal study from Takeda et al proved that there was a lack of correlation between DWS and LV systolic function, wall thickness at the beginning of diastole, LV chamber size, indices derived from the transmitral flow velocity curves as well as preload alteration, recent clinical studies (43,46,47,50,53) found that DWS may not be a pure measure of diastolic function since it also correlates with systolic function. Therefore, DWS may be considered as an overall marker of cardiac performance, including systolic and diastolic mechanics.…”
Section: The Epicardial Movement Index (Emi) and Diastolic Wall Strai...mentioning
confidence: 99%
“…Similarly, Kamimura D et al (49) in 2017 found DWS to be significantly associated with HF symptoms in patients with AS with preserved ejection fraction (OR: 0.91, CI:0.86-0.96, P<0.005). Immediately thereafter, in 2018,Kamimura D et al (50) found both continuous and categorical DWS were independently associated with incident HF after adjustment for traditional risk factors and incident coronary artery disease (HR 1.21, 95%CI 1.04-1.41 for 0.1 decrease in continuous DWS, P= 0.014; HR 1.40, 95%CI 1.05-1.87 for the smallest DWS quintile vs other combined quintiles, P = 0.022), and in 2019 a study by Tsujimoto S, et al (51) showed low DWS ([?] 0.33) was a significant independent predictor of cardiovascular events after adjusting for cardiovascular comorbidities in a multivariable model (HR: 1.87, 95% CI 1.04-3.36, P=0.04).…”
Section: The Epicardial Movement Index (Emi) and Diastolic Wall Strai...mentioning
confidence: 99%